Equity valuation : the Home Depot, Inc. - Nora, Manuel Pontes Caetano (2020)
The main objective of this study is to determine the target share price for The Home Depot, Inc. the leading company in the home remodeling industry in North America, thus issuing a recommendation whether to buy, hold or sell a stock position in the company. Initially, one started by scrutinizing the company’s strategic position, the market in which it operates, and the key drivers influencing the industry, ending with an analysis of the current crisis that is plaguing the United States and its possible outcomes. Moreover, the company’s financial reality was addressed and the prospect assumptions for the company were discussed and modeled using the DCF-method through WACC reaching a 12-month target share price of $263.9. A Relative Valuation was computed to complement and compare with the price reached from the previous method, concluding that this price is in the range of what the market is paying for the company’s peers (comparables). Afterward, comparing the target price to the market value on the 30th of April 2020 ($221.6), the investor would be exposed to a +22 percent return, thus a buy recommendation is issued. Finally, these results when compared to the equity research issued by Credit Suisse on the 1st of April 2020 make clear that the investment bank takes a more conservative position concerning the target price for the company (hold position).